2012
DOI: 10.1002/jbm.a.34174
|View full text |Cite
|
Sign up to set email alerts
|

Stirred flow bioreactor modulates chondrocyte growth and extracellular matrix biosynthesis in chitosan scaffolds

Abstract: The aim of this study is to show the favorable effect of simple dynamic culture conditions on chondrogenesis of previously expanded human chondrocytes seeded in a macroporous scaffold with week cell-pore walls adhesion. We obtained enhanced chondrogenesis by the combination of chitosan porous supports with a double micro- and macro-pore structure and cell culture in a stirring bioreactor. Cell-scaffold constructs were cultured under static or mechanically stimulated conditions using an intermittent stirred flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, mechanical stimulation is beneficial in the chondrogenesis [ 27 ]. Dynamic culture in spinner flasks has been suggested to be able to apply beneficial mechanical stimulation on chondrocytes [ 21 , 22 ]. Therefore, in the present study, whether combining 3D and dynamic culture would be beneficial for maintaining the chondrocyte phenotype during in vitro culture was proposed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, mechanical stimulation is beneficial in the chondrogenesis [ 27 ]. Dynamic culture in spinner flasks has been suggested to be able to apply beneficial mechanical stimulation on chondrocytes [ 21 , 22 ]. Therefore, in the present study, whether combining 3D and dynamic culture would be beneficial for maintaining the chondrocyte phenotype during in vitro culture was proposed.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it was reported that in response to the hydrostatic pressure, chondrocytes encapsulated in alginate gel beads secreted more glycosaminoglycans (GAG), a characteristic cartilaginous ECM component [ 20 ]. Additionally, fluid shear force in a spinner flask was implicated in stimulating ECM production by chondrocytes seeded in chitosan scaffolds [ 21 ]. Recently, Lee et al found that culture of cellular aggregates of dedifferentiated chondrocytes in a spinner flask was able to induce the redifferentiation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the emergence of recombinant collagen extracted from plants has important advantages as a scaffold in its own right or if used to functionalize the surfaces of the materials above. Furthermore, these materials have been modified, either as microspheres or bulk, to possess the porosity necessary for diffusion of nutrients through dynamic or static bioreactors (Oh et al, 2009;Wu et al, 2011;García Cruz et al, 2012;Varley et al, 2017;Huang et al, 2018;Specht et al, 2018). In order to scale an animal-free product with similarities to that of native animal tissue, the need for fetal bovine serum, costeffective engineering processes, antibiotic dependence, scaffold development, and cell line(immortalized vs. primary and cell co-culture) needs to be addressed (Specht et al, 2018;Stephens et al, 2018;Lynch and Pierrehumbert, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…5 All specimens were coated with a conductive layer of sputtered gold. An accelerating voltage of 20 kV was used to obtain micrographs.…”
Section: Methodsmentioning
confidence: 99%
“… 3 Different strategies can improve the chondrogenic ability of chitosan, such as its conjugation to transforming growth factor-beta (TGF-β; alone or encapsulated in microparticles), association with hydrogels including type II collagen or platelet-rich plasma (PRP), or the use of specific bioreactors. 4 6 …”
Section: Introductionmentioning
confidence: 99%